Resilience in shock and swim stress models of depression - Drugan, Robert C.; Christianson, John P.; Warner, Timothy A.; Kent, Stephen (Frontiers in Behavioral Neuroscience, 2013)
Experimental models of depression often entail exposing a rodent to a stressor and subsequently characterizing changes in learning and anhedonia, which may reflect symptoms of human depression. Importantly, not all people and not all laboratory rats exposed to stressors develop depressed behavior; these “resilient” individuals are the focus of our review. Herein we describe research from the “learned helplessness” and “intermittent swim stress” models of depression in which rats that were allowed to cope with the stressor appear to be behaviorally and neurochemically similar to rats that were not allowed to cope yet appeared resilient in behavioral tests. For example, rats exposed to inescapable tailshock, but do not develop learned helplessness, exhibit altered sensitivity to the behavioral effects of GABAA receptor antagonists and reduced in vitro benzodiazepine receptor ligand binding. This pattern suggested that resilience might involve activation of an endogenous benzodiazepine-like compound, possibly an allostatic modulator of the GABAA receptor like allopregnanolone. From the intermittent swim stress model, we have observed in resilient rats protection from stressor-induced glucocorticoid increases and immune activation. In order to identify the neural mediators of these correlates of resilience, non-invasive measures are needed to predict the resilient or vulnerable phenotype prior to analysis of neural endpoints. To this end, we found that ultrasonic vocalizations (USVs) appear to predict the resilient phenotype in the intermittent swim stress paradigm. We propose that combining non-invasive predictive measures, such as USVs with biological endpoint measures, will facilitate future research into the neural correlates of resilience.